2017
DOI: 10.18632/oncotarget.15786
|View full text |Cite
|
Sign up to set email alerts
|

Hobnail variant of papillary thyroid carcinoma: molecular profiling and comparison to classical papillary thyroid carcinoma, poorly differentiated thyroid carcinoma and anaplastic thyroid carcinoma

Abstract: BackgroundAs a rare but aggressive papillary thyroid carcinoma (PTC) variant, the genetic changes of hobnail variant of PTC (HVPTC) are still unclear.ResultsThe prevalence of HVPTC was 1.69% (18/1062) of all PTC diagnosed in our cohort. 73 samples from 55 patients (17 HVPTC, 26 CPTC, 7 PDTC and 5 ATC) were successfully analyzed using targeted NGS with an 18-gene panel. Thirty-seven mutation variant types were identified among 11 genes. BRAF V600E mutation was the most common mutation, which is present in almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
1
32
1
5
Order By: Relevance
“…Teng et al . reported 17 cases of hobnail variant PTC in a Chinese cohort, and the prevalence of BRAF V600E mutation was 16/17 (94%) cases, that of TP53 mutation was 3/17 (17.6%) and TERT mutation was noted in only 1/17 (5.9%) …”
Section: Cribriform‐morular Variant Ptcmentioning
confidence: 98%
See 1 more Smart Citation
“…Teng et al . reported 17 cases of hobnail variant PTC in a Chinese cohort, and the prevalence of BRAF V600E mutation was 16/17 (94%) cases, that of TP53 mutation was 3/17 (17.6%) and TERT mutation was noted in only 1/17 (5.9%) …”
Section: Cribriform‐morular Variant Ptcmentioning
confidence: 98%
“…201 Once again the author would like to emphasize is that there are significant differences in genetic profiles of thyroid cancers between Asian and Western patient populations, and the prevalence of BRAF V600E point mutation in Asian PTC cohorts is high compared to those reported from Western countries. 2,3,144,206,207…”
Section: Genetic Profiles and Molecular Diagnosis Of Thyroid Tumorsmentioning
confidence: 99%
“…BRAF V600E mutations are found in one‐third of these tumours . In hobnail variant PTC, BRAF V600E mutations are identified in a high percentage of cases; one study showed a 94.1% rate of BRAF V600E mutation . In diffuse sclerosing variant, which is uncommon and typically affects younger patients, RET/PTC rearrangements are found in a high percentage of cases while BRAF V600E mutations are rare in the range of 0%‐61%, although most studies suggest zero or very low rates of BRAF V600E mutation .…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%
“…In addition, a subset of hobnail variant demonstrates p53 mutations 6‐8. Molecular analysis of hobnail variant has shown that most have a BRAF V600E mutation 6‐8. Additionally, consistent with their aggressive clinical behaviour, most harbour secondary alterations, including TP53 mutations (seen in 15–55%), TERT promoter mutations (seen in approximately 45%) and PIK3CA mutations (seen in approximately 30%) 6‐8…”
Section: Introductionmentioning
confidence: 96%
“…Whereas 95% of differentiated thyroid carcinomas have a Ki67 proliferative index below 5%,5 the mean Ki67 proliferative index for hobnail variant is 10% 1. In addition, a subset of hobnail variant demonstrates p53 mutations 6‐8. Molecular analysis of hobnail variant has shown that most have a BRAF V600E mutation 6‐8.…”
Section: Introductionmentioning
confidence: 99%